Microstructure of Abdur's Stand-Up Comedy on the Stand Up Kompas TV YouTube Channel: A Critical Discourse Analysis by Van Dijk - Tomia, Sapryanti; Pattiasina, Petrus Jacob; Rumalean, Iwan (JENDELA PENGETAHUAN, 2023)
The purpose of this study is to describe the critical discourse analysis of Van's model Dijk on Abdur's Stand-up Comedy on Konpas TV Stand Up YouTube Channel. This study uses a type of descriptive qualitative research analysis technique, the critical discourse analysis of the Teum A Van Dijk model of data collection, using two techniques. Namely, the listening technique is the provision of data carried out by listening to videos on the use of language in Stand-Up Abdur and note-taking techniques. It is done by recording matters relating to the data in a Stand Up Abdur. The data source in this study was the Kompas TV stand-up YouTube channel. The data examined in this study is from Abdur's stand-up comedy, Indonesia, which is like an old ship. The results of the analysis obtained in this study are microstructure, which consists of the first four parts of semantics, namely background, detail, intent, presupposition and nominalization; the two syntaxes are coherence sentence forms and pronouns, and the three stylistic elements observed in the lexicon and the fourth rhetorically namely graphics and metaphors